If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(-5) * r = 5r + -3 Multiply -1 * -5 6 + 5r = 5r + -3 Reorder the terms: 6 + 5r = -3 + 5r Add '-5r' to each side of the equation. 6 + 5r + -5r = -3 + 5r + -5r Combine like terms: 5r + -5r = 0 6 + 0 = -3 + 5r + -5r 6 = -3 + 5r + -5r Combine like terms: 5r + -5r = 0 6 = -3 + 0 6 = -3 Solving 6 = -3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -9(-1+-4k)+k= | | 2(x+4)=6-1(3x-2)-1 | | Y=log[4](x^2-4x-21) | | x-7=-.25 | | 8x-29=-77+2x | | 7x-28=17+2x | | 2(6x+6)+8=8x+18 | | 3(2a-2)=2(3a-3) | | 5(3+6x)-4=41 | | 6x^2+33x+42=0 | | x^2-2x+56=0 | | x^2-2x+56=0 | | 6+6(-3-6z)= | | 8(6x-8)-8(2+3x)=-32 | | 5(10+6m)= | | -(6+4x)-8(8x-3)=-50 | | -7+5(2r-6)=-107 | | 5(3x+9)(5x-15)=0 | | (x-4)(x+1)=14 | | e^9x=3 | | 5(1+3b)+7(7-3b)=30 | | -5p+-4(-p+4)= | | 8-11=-13 | | -7x-3=-38 | | y*86=259 | | -5y+3z=12 | | -4(8+7h)+2= | | 9x+9=3y+6 | | 9+9x=6+3y | | 3ab-ab= | | 2x-=3 | | 3y+6=9x+9 |